Power Electronics Converters and Regulators - Dokić, Branko L.; Blanuša, Branko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is the result of the extensive experience the authors gained through their year-long occupation at the Faculty of Electrical Engineering at the University of Banja Luka. Starting at the fundamental basics of electrical engineering, the book guides the reader into this field and covers all the relevant types of converters and regulators. Understanding is enhanced by the given examples, exercises and solutions. Thus this book can be used as a textbook for students, for self-study or as a reference book for professionals.
Chapter 1 Introduction -- Chapter 2 Diodes and Transistors -- Chapter 3 Regenerative Switches -- Chapter 4 PWM DC/DC Converters -- Chapter 5 Control Modules -- Chapter 6 DC/AC Converters – Inverters -- Chapter 7 AC/DC Converters - Rectifiers -- Chapter 8 AC/AC Converters -- Chapter 9 Resonant Converters -- Chapter 10 Introduction to Multilevel Converters.
Keywords: Power electronics; Optical materials; Electronic materials; Energy systems; Power Electronics, Electrical Machines and Networks; Optical and Electronic Materials; Energy Systems